Statements New York 82 : Leading Contemporary Artists from France. - Hahn, Otto (Paris : Association Française d'Action Artistique, 1982)
Aillaud, Gilles ; Ben ; Bioulès, Vincent ; Blanchard, Rémy ; Boltanski, Christian ; Cane, Louis ; Combas, Robert ; Debré, Olivier ; Garouste, Gérard ; Hantaï, Simon ; Le Gac, Jean ; Malaval, Robert ; Messager, Annette ; Pagès, Bernard ; Pincemin, Jean-Pierre ; Poirier, Anne et Patrick ; Raysse, Martial ; Rouan, François ; Titus-Carmel, Gérard ; Venet, Bernar ; Viallat, Claude
Statements New York 82 : Leading Contemporary Artists from France. Ces expositions ont été organisées par l'Association Française d'Action Artistique sous les auspices du Ministère des relations extérieures. Artistic organizer : Otto Hahn, Art Critic. Barbara Gladstone Gallery, New York ; Castelli Graphics ; Robert Miller Gallery, New York ; Holly Solomon Gallery, New York ; Sonnabend Gallery, New York ; Leo Castelli Gallery, New York ; etc.
boek
Keywords: Frankrijk; New York